2006
DOI: 10.1128/iai.74.4.2015-2021.2006
|View full text |Cite
|
Sign up to set email alerts
|

Leukotoxin Confers Beta-Hemolytic Activity to Actinobacillus actinomycetemcomitans

Abstract: Actinobacillus actinomycetemcomitans is the etiologic agent of localized aggressive periodontitis, a rapidly progressing oral disease that occurs in adolescents. A. actinomycetemcomitans can also cause systemic disease, including infective endocarditis. In early work on A. actinomycetemcomitans workers concluded that this bacterium is not beta-hemolytic. More recent reports have suggested that A. actinomycetemcomitans does have the potential to be beta-hemolytic. While growing A. actinomycetemcomitans on sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 45 publications
2
98
1
Order By: Relevance
“…Interestingly, the ability of A. actinomycetemcomitans colonies to appear beta-hemolytic is dependent on the type of medium used (Fig. 3) and may explain why hemolysis was previously not observed (Balashova et al, 2006a). In contrast to cytolysis of WBCs, hemolysis appears to be non-specific, since human, sheep, and horse RBCs underwent lysis by LtxA, and hemolysis requires a higher dose of LtxA than the killing of WBCs.…”
Section: Ironmentioning
confidence: 89%
“…Interestingly, the ability of A. actinomycetemcomitans colonies to appear beta-hemolytic is dependent on the type of medium used (Fig. 3) and may explain why hemolysis was previously not observed (Balashova et al, 2006a). In contrast to cytolysis of WBCs, hemolysis appears to be non-specific, since human, sheep, and horse RBCs underwent lysis by LtxA, and hemolysis requires a higher dose of LtxA than the killing of WBCs.…”
Section: Ironmentioning
confidence: 89%
“…The remaining 2 genes, however, encoded less well recognized biofilm determinants-leukotoxin (ltxB [19]) and the DNA uptake transcriptional regulator TfoX (71). Leukotoxin is widely regarded as the primary virulence factor of A. actinomycetemcomitans, as it lyses both white and red blood cells (20), but recently it was also shown to control adherence. Specifically, disrupting ltxA diminishes tadA and pgaC expression and, as a result, binding to hydroxyapatite (calcium-based tooth mineral) (72).…”
Section: Discussionmentioning
confidence: 99%
“…To determine if iron plays a role in LtxA regulation, we assayed betahemolysis under excess-iron and iron-limiting conditions on Columbia agar with 5% sheep blood (3). We found that, compared to results obtained with media with no added iron, betahemolysis was suppressed when A. actinomycetemcomitans was grown on Columbia agar containing 300 M FeCl 3 (Fig.…”
mentioning
confidence: 97%